An acrylated isocyanonaphthalene based solvatochromic click reagent: Optical and biolabeling properties and quantum chemical modeling. (October 2016) - Nagy, Miklós; Rácz, Dávid; Nagy, Zsolt László; Nagy, Tibor; Fehér, Péter Pál; Purgel, Mihály; Zsuga, Miklós; Kéki, Sándor
Abstract: The optical and biolabeling properties of a novel molecule 1-(2-acryloyloxy-3-chloro-prop-1-yl)-amino-5-isocyanonaphthalene (ACAIN) is reported. In addition to being a real solvatochromic fluorophore it reacts quantitatively and rapidly with simple thiols in a thiol-ene click reaction. DFT calculations revealed a dark nonfluorescent state of ACAIN due to a close energy triplet state where electron transition can happen between the acrylic double bond and the aromatic core through an intramolecular hydrogen bond between the NH and CO moieties. The hydrothiolation reaction is accompanied by a 1.5–19 fold increase in fluorescence intensity depending on the solvent used owing to the saturation of the acrylic group. The quantum yield and reactivity of the molecules were found to be largely dependent on the substituent of the acryl moiety. The biolabeling properties were investigated in detail by fluorometry and electrospray ionization (ESI) mass spectrometry using cysteine, KAC as a simple tripeptide and BSA as a model protein. Graphical abstract: Highlights: Acrylated isocyanonaphthalene based solvatochromic click reagent was prepared. Reacts easily and quantitatively with a range of different thiols. The emission intensity significantly increases during the hydrothiolation reaction. The biolabeling abilities were demonstrated using biomolecules with free thiol group. DFT calculations revealed an internal acryl-naphthalene electron transfer.